Pacing in Olympic track races: Competitive tactics versus best performance strategy - Thiel, C.; Foster, C.; Banzer, W.; de Koning, J. (Journal of Sports Sciences, 2012)
The purpose of this study was to describe pacing strategies in the 800 to 10,000-m Olympic finals. We asked 1) if Olympic finals differed from World Records, 2) how variable the pace was, 3) whether runners faced catastrophic events, and 4) for the winning strategy.